PROFIL KOMPETENSI INSTRUKTUR AEROBIK (STUDI DESKRIPTIF PADA GURU PENDIDIKAN JASMANI DI KOTA BANDUNG) - Fitri, Mustika (Departement of Sports Education, Faculty of Sport Sciences Yogyakarta State University, 2008)
The target of this research was to know the profile of interest of instructor practice gymnastic aerobic in Town Bandung. Research method used in this research was descriptive method as a mean to depict an event at the time of now which look in a situation. In this research, data obtained to be collected, compiled, explained, and analyzed to specify conclusion, because this research wish to express problem that happened at a period to now that is instructor interest profile practice gymnastic aerobic. The population and sample of research of taken as source of information of teachers of physical education exercising gymnastic of aerobic center Fitness of Hotel Jayakarta, Majesty and Bikasoga Bandung. Research instrument in this research is questionnaire to measure instructor interest practice gymnastic aerobic. Enumeration and data processing use percentage technique. As for result of its enumeration shall be as follows: sub of cognate variable own score equal to 1605 or 71.33% from ideal score, affective own score equal to 1480 or 70.48% from ideal score, and psychomotor own score equal to 2658 or 70.88% from ideal score. Its conclusion is profile of interest of instructor practice gymnastic aerobic in Town Bandung earn indication through sub of cognate variable. While other aspect are psychomotor and affective. Matter this means to know interest of instructor practice gymnastic aerobic in Town of Bandung earn seemly its cognate ability later on ability of psychomotor and affective. Pursuant to result of processing and data analyses, hence conclusion from result of this research either through public and also special: â€œprofile of Interest of instructor practice gymnastic aerobic in Town of Bandung is included in good criterion.â€ This matter relied on acquirement of score of actual equal to 5743 or 70.90% from ideal score Kata kunci: instruktur, senam aerobic, guru penjas.